2016
DOI: 10.1680/adcr.14.00079
|View full text |Cite
|
Sign up to set email alerts
|

Temperature rise and initial shrinkage of alkali-activated fly ash cement pastes

Abstract: This paper reports on core temperature development and initial shrinkage of fly ash cement pastes activated with sodium hydroxide solution at different concentrations during elevated-temperature curing at 60°C. The results indicate that a high sodium hydroxide concentration might result in a substantial rise in the core temperature of samples, dependent on the mould size and ratio of paste to oven volume. An increase in alkali concentration was also found to increase the initial shrinkage of the pastes during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…For instance, Rovnanik [28] reported that GP specimens stored between 40 and 80 • C exhibited higher early-age strengths, as compared to companion specimens cured at ambient temperature. Similar conclusions were drawn by Kuenzel et al [29] and Shekhovtsova et al [30], who found that the increased curing temperature favored the strength development at early and late ages.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…For instance, Rovnanik [28] reported that GP specimens stored between 40 and 80 • C exhibited higher early-age strengths, as compared to companion specimens cured at ambient temperature. Similar conclusions were drawn by Kuenzel et al [29] and Shekhovtsova et al [30], who found that the increased curing temperature favored the strength development at early and late ages.…”
Section: Introductionsupporting
confidence: 87%
“…The prisms were demolded after 24 h and stored side-by-side in a closet where ambient temperature and RH were 23 ± 3 • C and 90% ± 5% RH, respectively, until testing time after 7 and 28 days. Earlier studies showed that the complete immersion of GP specimens in water detrimentally alters the development of strengths [28][29][30].…”
Section: Testing Methods and Proceduresmentioning
confidence: 99%
“…The production of hybrid cement requires less clinker than that for ordinary Portland cement, leading to a decrease in CO 2 emissions per tonne of hybrid cement manufactured. Hybrid alkaline cements is often preferred over their alkali activated counterparts because its hydration occurs at ambient temperature, and its production do not require the addition of highly alkaline chemicals, but rather rely on a safe source of alkali formed in situ (sodium hydroxide) to facilitate both the dissolution of any amorphous phases present in the source materials [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The papers are concerned with early-age performance through to long-term durability, while covering both applied fields and fundamental studies.The first paper, by Shekhovtsova et al (2016), investigates the temperature rise and early-age performance of alkaliactivated fly ash geopolymeric systems; continuing the work of this group in the field of heat-cured alkali-activated systems (Shekhovtsova et al, 2015). They show that the exothermic alkali activation of fly ash geopolymers can affect curing temperatures, especially at high alkali contents or in large samples.…”
mentioning
confidence: 99%